Você está na página 1de 367

 

 

 

 

T = 0

T

= 0

 

 

B hf

 

 

 

 

 

H

 

χ

 

B

 

χ

H

 

 

B

 

 

H B

 

1

 

1

 

M 1

 

 

M

 

 

χ

 
 

 

 
 

 

 
 

 

 
 

2+

L, S J µ L µ S µ J

 
 

Z

B J (x) x

 

J = 1/2,

3/2,

5/2

3+ 3+

 

3+ B/T

 

4f

 

(M T /M 0 )

 

B/T

 

 

M (T )

(M 0T /M 00 ) T /T C

H J = 1/2

J

T

/

J 12 > 0

J

T T C

kT /J

r

RbMnFe 3

T T 3/2

 

/

3d 4f 5f

Z

0

 

B 0

 

3d

T /T C /E F

T /T C /E F

T = 0 /E F

2

M × H

θ

 

θ

o

H

J r

P

P

T

σ = (g 1)J

I = 3/2

I =

2 1

1/T 2 T

T R

T s

T

1

π/2

π/2

π/2 π

59 2

86 14

147

2 17

59

 

 

x

 

 

 

d

 

3 +

 

 

 
 

1

F = 1vχ(q)

d s